Інноваційна діяльність у медичній освіті США (1910–1940 рр.) - Куліченко, Алла Костянтинівна; Kulichenko, Alla (Суми: СумДПУ, 2020)
У статті висвітлено інноваційну діѐльність у медичній освіті США під час першого поколіннѐ реформ (1910–1940 рр.). У розвідці автор зазначаю, що відправноя точкоя розвитку інноваційної діѐльності закладів медичної освіти США стала «Доповідь» Флекснера у 1910 р. Як наслідок, до 1920-х рр. відбувсѐ переглѐд американської медичної освіти, а саме з’ѐвилисѐ чіткі вимогу до вступу, чотири роки навчаннѐ безпосередньо в медичній школі, науково-оріюнтований навчальний план, аналіз фахової наукової літератури тощо. Кінець 1920-х рр. ознаменував поѐву стандартизованого тестуваннѐ длѐ вступу до закладів медичної освіти. У 1930-х рр. було створено організації вузькопрофільних спеціалістів длѐ їх професійного зростаннѐ. 1940-ві рр. були пов’ѐзані з «Доповіддя» Вайскоттена. Social development is connected with progress, which in turn depends on the modernization of a particular area of human activity with the help of reforms. Thus, since the beginning of the 20th century, the USA implemented many transformations, eventually becoming the world leader. It was, however, an extremely difficult way. it should be noted that initially there was a decrease in a large number of private medical schools for everyone willing to be a doctor but with no wish to further improve his/her professional knowledge. Finally, there was an emergence of medical schools as parts of reputable American universities with specific entry requirements, a profession-oriented curriculum and a combination of theory and practice in the form of scientific research. Therefore, during the process of upgrading Ukrainian medical education, it is necessary to analyze the experience of innovative activity of the American medical schools in the context of the US educational reforms. The aim of the paper is to highlight innovative activity in the US medical education during the first generation of reforms (1910s – 1940s). In this paper, the author uses such methods as (i) search-bibliographic and chronological ones – to study and systematize scientific and pedagogical literature on the subject of innovative activity in the American medical education during the first 40 years of the 20th century; (ii) pedagogical reconstruction – to reproduce the historical and pedagogical reality in the US medical education from 1910 to 1940. Moreover, the author notes that the Flexner Report dated 1910 was the starting point to develop innovative activity of the US medical education. As a result, in the 1920s, there were strict entry requirements, four years of study in medical schools, a science-oriented curriculum, professional scientific literature, etc. The late 1920s marked the emergence of a standardized test for admission to medical schools. In the 1930s, organizations for medical experts were established to help them grow professionally. The 1940s were connected with the Weiscotten Report. The study covers only a part of aspects of the problem. Concerning the prospects of further research, the plan is to describe the Weiscotten Report that deals with innovative activity in the American medical education from 1934 to 1939.
Innovative activity in US medical education (1910s–1940s)
Keywords: американська медична освіта; освітні реформи; інноваційна діяльність; медичні школи США; «Доповідь» Флекснера; «Доповідь» Вайскоттена; науково-орієнтований навчальний план; фахова наукова література; American medical education; educational reforms; innovations; US medical schools; Flexner Report; Weiscotten Report; science-oriented curriculum; professional scientific literature